AGR2 oncoprotein inhibits p38 MAPK and p53 activation through a DUSP10‐mediated regulatory pathway. Issue 5 (17th December 2015) - Hrstka, Roman; Bouchalova, Pavla; Michalova, Eva; Matoulkova, Eva; Muller, Petr; Coates, Philip J.; Vojtesek, Borivoj
Abstract : The tumor suppressor p53 plays a key role in malignant transformation and tumor development. However, the frequency of p53 mutations within individual types of cancer is different, suggesting the existence of other mechanisms attenuating p53 tumor suppressor activity. Changes in upstream regulators of p53 such as MDM2 amplification and overexpression, expression of viral oncoproteins, estrogen receptor signaling, or changes in p53 transcriptional target genes were previously described in wild‐type p53 tumors. We identified a novel pathway responsible for attenuation of p53 activity in human cancers. We demonstrate that AGR2, which is overexpressed in a variety of human cancers and provides a poor prognosis, up‐regulates DUSP10 which subsequently inhibits p38 MAPK and prevents p53 activation by phosphorylation. Analysis of human breast cancers reveals that AGR2 specifically provides a poor prognosis in ER+ breast cancers with wild‐type p53 but not ER‐ or mutant p53 breast cancers, and analysis of independent data sets show that DUSP10 levels also have prognostic significance in this specific sub‐group of patients. These data not only reveal a novel pro‐oncogenic signaling pathway mediating resistance to DNA damaging agents in human tumors, but also has implications for designing alternative strategies for modulation of wild‐type p53 activity in cancer therapy. Highlights: The transcription factor p53 is the most intensively studied tumor suppressor. AGR2‐dependent signaling pathway blocks wt p53 transcriptional activity. p53 activity is impaired via DUSP10 up‐regulation causing inhibition of p38 MAPK. AGR2 signaling towards p53 was demonstrated both in vitro and in vivo.